1992
DOI: 10.1172/jci116043
|View full text |Cite
|
Sign up to set email alerts
|

Balloon angioplasty enhances the expression of angiotensin II AT1 receptors in neointima of rat aorta.

Abstract: Clin. Invest. 1992.90:1707-1712

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
64
0
2

Year Published

1994
1994
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(74 citation statements)
references
References 36 publications
8
64
0
2
Order By: Relevance
“…Ang II receptor expression has been demonstrated in the neointima of experimentally injured vessels 8 and vascular smooth muscle cells of human atherosclerotic plaques. 6 The critical role of tissue Ang II receptor expression and activation in the pathobiology of intimal hyperplasia is supported by the observation of prevention of neointimal hyperplasia in response to vascular injury and atherosclerosis by ACE inhibitors and AT 1 receptor antagonists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ang II receptor expression has been demonstrated in the neointima of experimentally injured vessels 8 and vascular smooth muscle cells of human atherosclerotic plaques. 6 The critical role of tissue Ang II receptor expression and activation in the pathobiology of intimal hyperplasia is supported by the observation of prevention of neointimal hyperplasia in response to vascular injury and atherosclerosis by ACE inhibitors and AT 1 receptor antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…6 Rakugi et al 7 demonstrated induction of the angiotensinconverting enzyme (ACE) in the neointima of injured blood vessels and speculated on its possible role in restenosis after angioplasty. Viswanathan et al 8 described increased Ang II receptor expression in the neointima after vascular injury, which would facilitate the action of Ang II. ACE has also been found in vascular smooth muscle cells in intimal lesions and in macrophages and vascular smooth muscle cells in the fibroproliferative lesion of human atherosclerotic plaques from atherectomy, surgical, and postmortem specimens.…”
mentioning
confidence: 99%
“…2 Most of AII functions in the cardiovascular system are mediated through the AT1 receptor, and in rodents they are mediated through the AT1a receptor. [3][4][5][6] Recently, many reports have suggested that AII is involved in other functions, such as apoptosis, vascular remodeling, and inflammation. [7][8][9] As regards vascular remodeling, several studies have shown that AII promotes proliferation, migration, and growth factor synthesis in several types of vascular cells, including smooth muscle cells and pericytes.…”
mentioning
confidence: 99%
“…In injured arteries, components of renin-angiotensin system are upregulated, such as renin, 8 angiotensinogen, 9 ACE, 10,11 and Ang II receptors. 12,13 We have developed a mouse model of vascular disease induced by polyethylene cuff placement around the femoral artery, in which ACE and the AT 1 receptor are upregulated, followed by neointimal thickening. 13 Estrogen replacement therapy suppresses the prevalence of cardiovascular disease in postmenopausal women 14 and reduces plasma LDL cholesterol and increases HDL cholesterol levels.…”
mentioning
confidence: 99%